A Prospective Observational Study on Medication Reconciliation at Discharge in A Tertiary Care Hospital - S, Satish; P, Snoviya Suresh Babu; A, Ramakrishna Shabaraya (Indian Journal of Pharmacy Practice)
Introduction: Medication reconciliation is crucial in healthcare to reduce medication discrepancies especially during transitions in care such as during discharge. This process aims for accurate medication management and improve patient safety by addressing discrepancies such as omissions and unclear instructions, ultimately reducing morbidity and enhancing patient well-being. Objectives: To evaluate the number and type of medication discrepancies identified during discharge medication reconciliation. Materials and Methods: A prospective observational study was carried out from January 2023 to June 2023 in a Tertiary care hospital. Results: Of the 255 patients (132 men, 123 women) included in the study a total of 412 discrepancies were identified of which 191 were unintentional. Majority occurred due to drug omission (53.92%), other include, altered dose (26.72%), altered frequency (7.8%), drug duplication (4.1%). Majority of the errors were identified from general medicine (49.74%) and cardiology department (17.28%). Majority of unintentional errors, were under category C (52.54%). Conclusion: Medication discrepancies at discharge were prevalent for patients admitted in hospital. Medication reconciliation processes have a high potential to identify clinically important discrepancies for all patients.
Keywords: Medication reconciliation; Medication discrepancies; Discharge; Errors